The difficulties identifying materials used in preserved traces of decorations on wooden artefacts from the Old Town in Elbląg, 26 Bednarska Street, site XXXII (north of Poland). Remarks on multi-analytical non-destructive studies - Miazga, Beata; Sieńkowska, Urszula; Kubiak-Nowak, Dominik; Michalik, Jakub; Grupa, Małgorzata (Archaeologia Historica Polona, 2025)
In medieval archaeological material, artefacts with traces of decorations on the surface are rare; this caused researchers to conduct multiple analytical studies on objects unearthed in Elbląg. In 2022, in the Old Town at 26 Bednarska Street, site XXXII, an oval box with a colourful floral motif and fragments of a stave-built bowl painted light pink on the inside were found. The difference in the colour of the wooden surfaces was revealed only after conservation procedures. Non-destructive and non-invasive studies were performed by means of an X-ray fluorescence micro-spectrometer Spectro Midex SD, a scanning electron microscope Hitachi TM4000plus coupled with an EDS spectrometer by Oxford Instruments, a portable spectrometer Tracer 5i, a digital X-ray machine Multix Impact C by Siemens, and two CT scanners Siemens Somatom go.TOP and Nikon Metrology Europe (XT H 225).